L'epistolario di Ludovico Beccadelli. Con un'appendice sui carteggi beccadelliani dispersi (Quaderni di Gargnano, 2018)
Beccadelli (1501-1572) was a leading light in the political and religious milieu of his day. Variously secretary to Cardinal Contarini, papal nuncio to Venice and archbishop of Ragusa in Dalmatia, Beccadelli, who also took part in the last sessions of the Council of Trent, dedicated his life to the service of the Church. At the same time, he was an active participant in the cultural life of the time, having studied at the Universities of Bologna and Padua. His letters offer scholars illuminating details of the cultural and social context of his world, especially the Roman curia, along with a revealing self-portrait of the author. The Appendix lists the few published letters (in ancient and modern collections) along with the manuscripts of unpublished letters (both sent and received) that Tarsi found in the course of her research.
Keywords: Epistolography; Manuscript Studies; Ludovico Beccadelli; Self-portrait